Mexico - Improving Productivity for the Urban Poor - World Bank (World Bank, 2012)
This report is part of an ongoing dialogue between the World Bank and Secretaria de Desarrollo Social (SEDESOL) on poverty reduction. It builds on the findings and messages of the World Bank poverty programmatic reports, which included a poverty assessment, detailed follow-up analysis of urban and rural poverty, social protection, and poverty and decentralization. This report responds to a request from the SEDESOL for support in refining its programmatic approach to poverty reduction via further analysis and more detailed recommendations and guidance regarding the next generation of poverty reduction/social development programs. This report is the first of three technical pieces agreed with SEDESOL as part of the work program on increasing the productivity of the poor. The two remaining pieces are: a) reviewing international evidence and experience on selected policies and programs; and b) developing the implication for social development/poverty reduction policies and programs in Mexico. This report begins with a short summary of main findings. Chapter one analyzes recent trends in urban poverty, with emphasis in the recovery in poverty levels after the mid-1990s peso crisis. Chapter two discusses the characteristics of the urban poor and their labor market performance. Chapter three reviews the legal and regulatory environment and its affects on labor market performance. Chapters four to six provide assessments of selected interventions to improve the income and job opportunities of the poor, and offers suggestions that could better their results. The last chapter concludes and discusses areas of future work.